Em busca da estabilização numa rede sociotécnica: a intervenção de robôs conversacionais (bots) em decisões comerciais - Eduardo Augusto de Andrade (2021)
This is an investigation into a data-driven business environment comprised of a SaaS company and a real estate agency. In this environment composed of human and non-human actors, a complex network with heterogeneous interests was configured. In this context, the research aimed to investigate how the temporary stabilization process of a commercial sociotechnical network influenced by conversational bots takes place. The conceptual framework was based on studies of users and informational behavior, decision making and Actor-Network Theory. The latter was used as a theoretical-methodological contribution. In the empirical field, semi-structured interviews, document analysis and systematic observation were adopted. The results point to a hybridity in which the influence of humans and non-humans interferes in the network where they are inserted, in order to shape the informational behavior of information users in the decision-making process. A synchronous and mimetic behavior of the client user of conversational platforms mediated by bots was identified, which was called synchromimicry. Moreover, the instability in the network proved to be farther from being achieved than the actors involved in it intended, due to constant improvements that promote new controversies. Finally, the research also revealed that the intuitive aspect, for a long time the only guiding factor in the decision-making process of the commercial agent, has its applicability reduced in face of the guidelines based on data from decision support systems.